Combined Administration of Andrographolide and Angiotensin- (1-7) Synergically Increases the Muscle Function and Strength in Aged Mice - Vilos-Ortiz, C; Cabello-Verrugio, C; Abrigo, J (BENTHAM SCIENCE PUBL LTD, 2022)
Background: Sarcopenia is a progressive and generalized skeletal muscle disorder characterized by muscle weakness, loss of muscle mass, and decline in the capacity of force generation. Aging can cause sarcopenia. Several therapeutic strategies have been evaluated to prevent or alleviate this disorder. One of them is angiotensin 1-7 [Ang-(1-7)], an anti-atrophic peptide for skeletal muscles that regulates decreased muscle mass for several causes, including aging. Another regulator of muscle mass and function is andrographolide, a bicyclic diterpenoid lactone that decreases the nuclear factor kappa B (NF-kappa B) signaling and attenuates the severity of some muscle diseases. Objective: Evaluate the effect of combined administration of Ang-(1-7) with andrographolide on the physical performance, muscle strength, and fiber s diameter in a murine model of sarcopenia by aging. Methods: Aged male mice of the C57BL/6J strain were treated with Andrographolide, Ang-(1-7), or combined for three months. The physical performance, muscle strength, and fiber s diameter were measured. Results: The results showed that aged mice (24 months old) treated with Ang-(1-7) or Andrographolide improved their performance on a treadmill test, muscle strength, and their fiber s diameter compared to aged mice without treatment. The combined administration of Ang-(1-7) with andrographolide to aged mice has an enhanced synergically effect on physical performance, muscle strength, and fiber s diameter. Conclusion: Our results indicated that in aged mice, the effects of andrographolide and Ang-(1-7) on muscle function, strength, and fiber s diameter are potentiated.